Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

How would I factor $-x^3+x^2+12$? Grouping doesn't work and I tried synthetic division but none of the possible zeros worked for me. I had $\pm1,\pm2, \pm4, \pm6, \pm12 $. What am I missing?

share|cite|improve this question
So probably you need to know its real/complex roots to be able to factor, can't do much without that. I don't see any other way to approach this. – Mark Fantini Nov 23 '13 at 22:59
WolframAlpha gives approximately $-(x-2.67589) (x+(0.837944-1.94482 i)) (x+(0.837944+1.94482 i))$. – MasterOfBinary Nov 23 '13 at 23:00
$x$ is not an integer, one real root is $x = 2.67588866957270$, the other two are $x = -0.83794433478635 \pm 1.94482410365933 i$ – K. Rmth Nov 23 '13 at 23:01
We get questions like these all the time. Not every polynomial is factor-able into integers. – bwv869 Nov 23 '13 at 23:06
I knew that because I couldn't solve it that it must have been unfactorable. I figured it would be a complex number. So basically theres no way of solving this by hand right? – Ruth Gutierrez Nov 23 '13 at 23:10

You cannot factor this to find the roots. One way to solve the cubic is to first convert it into a depressed cubic (without the $x^2$ term). To do this, we have to make the substitution $x=y-\dfrac{b}{3a}$. $$-x^3+x^2+12=0$$ $$-(x^3-x^2-12)=0$$ $$=-\left[\left(y-\left(\dfrac{1}{3}\right)^3\right) - \left(y-\left(\dfrac{1}{3}\right)^2\right) + 12\right]=0$$ Expanding the expression and simplifying gives us: $$-\left(y^3 + \dfrac{1}{3}y + \dfrac{326}{27}\right)=0$$ $$y^3+\dfrac{1}{3}y + \dfrac{326}{27}=0$$ $$y^3+\dfrac{1}{3}y = -\dfrac{326}{27}$$ The depressed cubic is now in the form $y^3 + Ay = B$. To solve this we have to assume two variables, $s$ and $t$, with the condition that: $$3st = A$$ $$s^3 - t^3 = B$$ $y = s-t$ will be a root of the cubic. This is proved by substituting $(s-t)$ into $y$, $3st$ into $A$, and $s^3-t^3$ into $B$. You can do this on your own time; I will not write the proof here because I am lazy.

Let's derive a formula to convert our cubic into a quadratic. We first solve $3st = B$ for $s$, and substitute it into $s^3-t^3=B$ $$s = \dfrac{A}{3t}$$ $$\left(\dfrac{A}{3t}\right)^3 - t^3 = B$$ $$\dfrac{A^3}{27t^3} - B - t^3 = 0$$ Multiply by $-t^3$ on both sides. $$-\dfrac{A^3}{27} + Bt^3 + t^3\cdot t^3 = 0$$ $$t^6 + Bt^3 - \dfrac{A^3}{27}$$ Finally, we make the substitution $u=t^3$ to obtain: $$u^2 + Bu - \dfrac{A^3}{27} = 0$$ Using our formula, we get: $$u^2 - \dfrac{326}{27}u - \dfrac{\frac{1}{9}}{27} = 0$$ Multiply by 27 on both sides. $$27u^2 - 326u - \dfrac{1}{9} = 0$$ Multiply by 9 on both sides. $$243u^2 - 2934u - 1 = 0$$ I can tell that the solution is not going to be pretty. Let's find the solution. $$u = \dfrac{2934 \pm \sqrt{2934^2 - 4(243)(-1)}}{2\times 243}$$ $$u = \dfrac{2934 \pm \sqrt{8609328}}{486}$$ $$u = \dfrac{2934 \pm 4\sqrt{556833}}{486}$$ $$u = \dfrac{1467 \pm 2\sqrt{556833}}{243}$$ Remember $u=t^3$. Also discard the negative square root. $$t^3 = \dfrac{1467 + 2\sqrt{556833}}{243}$$ $$t = \sqrt[3]{\dfrac{1467 + 2\sqrt{556833}}{243}}$$ Substitute the value of t^3 into the equation $s^3 + t^3 = B$ to obtain $s$. $$s^3 + t^3 = -\dfrac{326}{27}$$ $$s^3 = -\dfrac{326}{27} - t^3$$ $$s^3 = -\dfrac{326}{27} - \dfrac{1467 + 2\sqrt{556833}}{243}$$ $$s = \sqrt[3]{-\dfrac{326}{27} - \dfrac{1467 + 2\sqrt{556833}}{243}}$$ $$s = \sqrt[3]{-\dfrac{326 + 1467 + 2\sqrt{56833}}{243}}$$ $$s = \sqrt[3]{-\dfrac{1793 + 2\sqrt{56833}}{243}}$$ Remember $y = s-t$: $$y = s-t$$ $$y= \sqrt[3]{-\dfrac{1793 + 2\sqrt{56833}}{243}} - \sqrt[3]{\dfrac{1467 + 2\sqrt{556833}}{243}}$$ Finally, remember $x = y - \dfrac{b}{3a}$: $$x = y - \dfrac{b}{3a}$$ $$x = \sqrt[3]{-\dfrac{1793 + 2\sqrt{556833}}{243}} - \sqrt[3]{\dfrac{1467 + 2\sqrt{556833}}{243}} - \dfrac{1}{3}$$ The solution to the cubic equation $-x^3 + x^2 + 12$ is (hopefully): $$\boxed{x = \sqrt[3]{-\dfrac{1793 + 2\sqrt{556833}}{243}} - \sqrt[3]{\dfrac{1467 + 2\sqrt{556833}}{243}} - \dfrac{1}{3}}$$ By the way, the mathematician Scipione del Ferro was the first person to invent a "cubic formula" using the method described above. In case you were wondering, the cubic formula is what it sounds like: a formula that can be used to solve cubic equations.

The roots of any cubic equation $ax^3 + bx^2 + cx + d = 0$ is: $$x = \sqrt[3]{\left(\dfrac{-b^3}{27a^3} + \dfrac{bc}{6a^2} - \dfrac{d}{2a}\right) + \sqrt{\left(\dfrac{-b^3}{27a^3} + \dfrac{bc}{6a^2}-\dfrac{d}{2a}\right)^2 - \left(\dfrac{c}{3a}-\dfrac{b^2}{9a^2}\right)^3}} + \sqrt[3]{\left(\dfrac{-b^3}{27a^3}+\dfrac{bc}{6a^2}-\dfrac{d}{2a}\right) + \sqrt{\left(\dfrac{-b^3}{27a^3}+\dfrac{bc}{6a^2}-\dfrac{d}{2a}\right)^2 - \left(\dfrac{c}{3a}-\dfrac{b^2}{9a^2}\right)^3}} - \dfrac{b}{3a}$$ I really, really do not think that you should memorize this formula because even if you do, it will be very, very inefficient.

share|cite|improve this answer

The polynomial is irreducible over the rationals. Why do you want to factor this equation? Can you post the problem in which you believe you have to factor this equation?

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.